2021
DOI: 10.4236/as.2021.125033
|View full text |Cite
|
Sign up to set email alerts
|

Local Taxonomy and Diversity of Chadian Sorghum [<i>Sorghum bicolor</i> (L.) Moench] Accessions

Abstract: The integration of local plant genetic resources into the breeding program is an asset for research. The objective of this study is to assess the diversity and analyze the management practices of cultivated sorghum. A questionnaire following a participatory approach was submitted to 675 producers in 45 villages. The cultivars collected were characterized using 9 qualitative descriptors. In total, 151 accessions and 191 names were inventoried. On average, 25.17 accessions per department and 3.36 accessions per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…This finding concurs with the studies of Sawadogo et al. (2014) in BurkinaFaso, Nadjiam (2021) in Chad, and Desmae et al. (2016) in Ethiopia, who reported that the majority of their germplasm collections had 25% glume cover.…”
Section: Discussionsupporting
confidence: 91%
“…This finding concurs with the studies of Sawadogo et al. (2014) in BurkinaFaso, Nadjiam (2021) in Chad, and Desmae et al. (2016) in Ethiopia, who reported that the majority of their germplasm collections had 25% glume cover.…”
Section: Discussionsupporting
confidence: 91%
“…D. Nadjiam (2021) production worldwide is 8,9 million tons from 14,4 million hectares. In Africa, Nigeria is the largest producer with 3,5 million tons (FAOSTAT, 2019).…”
Section: Research Articlementioning
confidence: 99%
“…D. Nadjiam (2021) This paper can be downloaded online at http://ijasbt.org & http://nepjol.info/index.php/IJASBT…”
Section: Conflict Of Interestmentioning
confidence: 99%